Characterization and Mapping of Spot Blotch in Triticum durum–Aegilops speltoides Introgression Lines Using SNP Markers - Kaur, Jashanpreet; Kaur, Jaspal; Dhillon, Guriqbal Singh; Kaur, Harmandeep; Singh, Jasvir; Bala, Ritu; Srivastava, Puja; Kaur, Satinder; Sharma, Achla; Chhuneja, Parveen (Frontiers in Plant Science, 2021)
Spot blotch of wheat is emerging as a major threat to successful wheat production in warm and humid areas of the world. Spot blotch (SB), also called leaf blight, is caused by Bipolaris sorokiniana, and is responsible for high yield losses in Eastern Gangetic Plains Zone in India. More recently, SB is extending gradually towards cooler, traditional wheat growing North-western part of the country which is a major contributor to national cereal basket. Deployment of resistant cultivars is considered as the most economical and ecologically sound measure to avoid losses due to this disease. In the present study, 89 backcross introgression lines (DSBILs) derived from Triticum durum (cv. PDW274-susceptible) X Aegilops speltoides (resistant) were evaluated against SB for four consecutive years, 2016-2020. Phenotypic evaluation of these lines showed a continuous variation in disease severity indicating that the resistance to SB is certainly quantitative in nature. Phenotypic data of DSBILs was further used for mapping QTLs using SNPs obtained by genotyping by sequencing. In order to identify QTLs stable across the environments, Best Linear Unbiased Estimates (BLUEs) and Predictions (BLUPs) were used for mapping QTLs based on stepwise regression-based Likelihood Ratio Test (RSTEP-LRT) for additive effect of markers and single marker analysis (SMA). Five QTLs, Q.Sb.pau-2A, Q.Sb.pau-2B, Q.Sb.pau-3B, Q.Sb.pau-5B, and Q.Sb.pau-6A linked to SB resistance were mapped across chromosomes 2A, 2B, 3B, 5B and 6A. Genes found adjacent to the SNP markers linked to these QTLs were literature mined to identify possible candidate genes by studying their role in plant pathogenesis. Further, highly resistant DSBIL (DSBIL-13) was selected to cross with a susceptible hexaploidy cultivar (HD3086) generating BC2F1 population. The QTL Q.Sb.pau-5B, linked to SNP S5B_703858864, was validated on this BC2F1 population and thus, may prove to be a potential diagnostic marker for spot blotch resistance.